Territorial Arrangements of Small and Medium‐Sized Towns from a Functional‐Spatial Perspective. (27th February 2017) - Sýkora, Luděk; Mulíček, Ondřej
Abstract: This contribution applies a functional‐spatial perspective to the study of small and medium‐sized towns. A methodology for functional analysis is developed and tested to identify towns, distinguish towns from cities, and detect town positionality within urban territorial arrangements, focusing on whether they are autonomous, networked with other towns or agglomerated with large cities. The methodology is used to compare settlement systems in two regions and two countries in Europe by looking at the existence and nature of networks between towns and cities and how towns perform in terms of population and jobs in respect of their belonging to different types of territorial arrangement.